Novel approaches to improving the chemical safety of the meat chain towards toxicants. (November 2015) - Engel, E.; Ratel, J.; Bouhlel, J.; Planche, C.; Meurillon, M.
Abstract: In addition to microbiological issues, meat chemical safety is a growing concern for the public authorities, chain stakeholders and consumers. Meat may be contaminated by various chemical toxicants originating from the environment, treatments of agricultural production or food processing. Generally found at trace levels in meat, these toxicants may harm human health during chronic exposure. This paper overviews the key issues to be considered to ensure better control of their occurrence in meat and assessment of the related health risk. We first describe potential contaminants of meat products. Strategies to move towards a more efficient and systematic control of meat chemical safety are then presented in a second part, with a focus on emerging approaches based on toxicogenomics. The third part presents mitigation strategies to limit the impact of process-induced toxicants in meat. Finally, the last part introduces methodological advances to refine chemical risk assessment related to the occurrence of toxicants in meat by quantifying the influence of digestion on the fraction of food contaminants that may be assimilated by the human body. Highlights: An overview of novel promising approaches to improving meat product chemical safety Toxicogenomics and nanotechnology for a more systematic control of meat chain Strategies to mitigate process-induced toxicants in meat Chemical risk assessment by quantification of toxicant bioaccessibility